Análise de influência do formato do agregado graúdo na resistência à compressão do concreto estrutural - Griebler, Matheus Francisco (2018)
Concrete is the most used structural material because it has important properties and characteristics and is suitable for a variety of purposes. It is a material made up of coarse and fine aggregates, binder and water, in which the study of the various components is extremely important because they influence the quality of the concrete. Thus, the research analyzes the influence caused by the difference in the shape of the basaltic aggregate in the properties of the usual concrete (fck = MPa) in fresh condition, analyzing the consistency by the slump test and, in the hardened state, analyzing the compressive strength. The dosage and the preparation of the specimens were carried out according to the Brazilian Portland Cement Association (ABCP). The results showed that the use of irregular aggregates is harmful in the fresh state and in the hardened state of the concrete, both in the workability and in the compressive strength.